The Christmas spirit : a novel - Macomber, Debbie (New York : Random House Large Print, 2022)
"Peter Armstrong and Hank Colfax are best friends, but their lives couldn't be more different. Peter, the local pastor who is dedicated to his community, spending time visiting the flock, attending meetings, and, with the holiday season approaching, preparing for the Christmas service and live nativity. As a bartender, Hank serves a much different customer base at his family-owned tavern, including a handful of lonely regulars and the local biker gang. When Peter scoffs that Hank has it easy compared to him, the two decide to switch jobs until Christmas Eve. To their surprise, the responsibilities of a bartender and a pastor are similar, but taking on the other's work is more difficult than either Peter or Hank expected. As the two begin to see each other in a new light--and each discovers a new love to cherish--their lives are forever changed"--
Keywords: Male friendship -- Fiction; Man-woman relationships -- Fiction; Clergy -- Fiction; Bartenders -- Fiction; Holidays -- Fiction; Friendship -- Fiction; Bars (Drinking establishments) -- Fiction; Christmas stories; Large type books; Large type books; Romance fiction; Christmas fiction; Novels